Transformasi Insentif Pajak dalam Era Global Minimum Tax : Systematic Literature Review - Panca Wisesa; Rindy Ladista; Diajeng Wulan; Kamadie Syafis (BISMA : Business and Management Journal, 2026)
The implementation of the Global Minimum Tax (GMT) under the OECD/G20 Pillar Two framework has raised concerns regarding the future role of tax incentives as instruments for attracting investment and maintaining international competitiveness. This study aims to analyze the transformation of tax incentives in the GMT era and its implications for developing countries. Using a Systematic Literature Review (SLR) approach, literature was collected from the Scopus database for the period 2020–2026 using the keywords “global minimum tax” and “tax incentives.” Following the PRISMA 2020 procedure, nine articles were selected and analyzed through coding, thematic categorization, narrative synthesis, and comparative analysis. The findings indicate that GMT reduces the effectiveness of rate-based tax incentives through the top-up tax mechanism, limiting the benefits of low-tax regimes. However, incentives linked to substantive economic activities remain relevant through the Substance-Based Income Exclusion (SBIE), productive investment, and employment creation. The study also finds that developing countries face greater challenges due to their dependence on fiscal incentives and limited institutional capacity. Overall, global tax competition is shifting from rate-based competition toward substance-based fiscal competition, requiring developing countries to strengthen institutional quality and non-fiscal competitiveness.